Web Based E-Learning System for C-Language - Hong, Lian Xi; Li, Chuan Mu (Applied Mechanics and Materials, 2013)
This paper introduces a Web-based tutoring system for computer programming that provides an integrated environment for web programming. The proposed system is web-based. It provides an online editor for writing, editing, updating, and executing programming code, so the students can execute examples and practical exercises online, it can help a student navigate through the online course materials, recommend learning goals, and generate appropriate reading sequences.. In addition, it provides auto complete and syntax highlighting in editing code, which could help students to remember the syntax more easily. The proposed system provides communication and interactive forum among students and teachers. And it provides the teachers with an online exam system. It monitors, collects and keeps information about students performance and activities. Therefore, teachers can use the recorded information to keep tracking of the students progress.